Marein alleviates myocardial fibrosis in diabetic mice - TIAN Yating, ZHANG Fang, ZHANG Boxiang, LI Tian (Jichu yixue yu linchuang, 2024)
Objective To study the effect of marein on myocardial fibrosis in diabetic mice. Methods Ten leptin receptor gene defective heterozygous (db/m) mice aged 5-6 weeks were selected as the control group and 30 diabetic mice with leptin receptor gene defective db/db were divided into: db/db group (db/db,n=10), metformin (Met) positive group (280 mg/kg daily,n=10) and marein drug intervention group (50 mg/kg,n=10). After continuous administration for 8 weeks, the cardiac morphological changes were observed by HE staining and Masson staining. The distribution and expression of vimentin were detected by immunohistochemistry method. The expression of fibronectin, vimentin, and transforming growth factor-β1(TGF-β1)protein in cardiac tissue was detected by Western blot. Results Myocardial fiber hypertrophy was observed in db/db group, and myocardial structural damage was improved in metformin group and marein group. Compared with db/m group, the expression of myocardial collagen fiber in db/db group increased (P＜0.01), while the expression of myocardial collagen fiber in metformin group and marein group decreased (P＜0.01). Compared with the control group, the expression of vimentin in myocardial tissue of db/db group was significantly increased(P＜0.01), while the expression of vimentin in metformin group and marein group was significantly decreased (P＜0.01). The expression of fibronectin, vimentin and TGF-β1 in db/db group was significantly increased as compared with those in db/m group (P＜0.01), while the expression of fibronectin, vimentin and TGF-β1 in metformin group and marein group were significantly decreased (P＜0.01). Conclusions Marein improves myocardial fibrosis in diabetic db/db mice.